Leading on empty : refilling your tank and renewing your passion - Cordeiro, Wayne (Minneapolis, Minn. : Bethany House, 2009)
"Practical help and encouragement for pastors experiencing burnout and depression"--Provided by publisher.
When the needle points to empty -- Forced to failure -- Power perfected in weakness -- Early warning signs -- Solitary refinement -- Finding the still waters -- The new perspective -- Seven lessons hard-learned -- Finding the way back home -- The intentional life -- Finding solitude in sabbaticals.
Includes bibliographical references (p. [213]-215).
Keywords: Clergy -- Job stress; Burn out (Psychology) -- Religious aspects -- Christianity; Clergy -- Mental health; Depression, Mental -- Religious aspects -- Christianity; Cordeiro, Wayne